2008
DOI: 10.1016/j.renene.2007.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations of a four-stroke single cylinder direct injection diesel engine operated on dual fuel mode with producer gas as inducted fuel and Honge oil and its methyl ester (HOME) as injected fuels

Abstract: In order to meet the energy requirements, there has been growing interest in alternative fuels like biodiesels, methyl alcohol, ethyl alcohol, biogas, hydrogen and producer gas to provide a suitable diesel oil substitute for internal combustion engines. Vegetable oils present a very promising alternative to diesel oil since they are renewable and have similar properties. Vegetable oils offer almost the same power output with slightly lower thermal efficiency when used in diesel engine [Srivastava A, Prasad R. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(63 citation statements)
references
References 25 publications
5
58
0
Order By: Relevance
“…The sampling interval of our measurement and analysis system was set to 0.25°crank angle (CA), 0.5°CA and 1°CA. The characteristic parameters of combustion process such as the timing of combustion, maximum combustion pressure, maximum pressure rise rate and corresponding phases were obtained [4,21,22] . The gasifier is of negative pressure downdraft type.…”
Section: Biogas-diesel Dual Fuel Engine and Experimental Setupmentioning
confidence: 99%
“…The sampling interval of our measurement and analysis system was set to 0.25°crank angle (CA), 0.5°CA and 1°CA. The characteristic parameters of combustion process such as the timing of combustion, maximum combustion pressure, maximum pressure rise rate and corresponding phases were obtained [4,21,22] . The gasifier is of negative pressure downdraft type.…”
Section: Biogas-diesel Dual Fuel Engine and Experimental Setupmentioning
confidence: 99%
“…EGT in dual fuel mode was higher than that of single fuel mode at all load conditions. This might be due to the excess of energy supplied to the engine in dual fuel mode (Banapurmath 2008). …”
Section: Brake Thermal Efficiency (Bte)mentioning
confidence: 99%
“…Many researchers have studied the combustion and emission characteristics of the dual-fuel engines fueled with gaseous-liquid fuels. Banapurmath et al (2008) tested a single cylinder, four stroke direct injection diesel engine with producer gas and honge oil and its methyl ester (HOME) in dual fuel mode and reported a slight reduction in thermal efficiency and increased smoke, HC and CO levels. Also HOME-producer gas operation showed improvement in heat release rate compared to neat honge oil-producer gas dual fuel operation.…”
Section: Introductionmentioning
confidence: 99%
“…Since bio-diesel contains 11% oxygen, it has a lower heating-value than fossil diesel [7]. If 100% biodiesel is used, then it is required to burn 5-6% more fuel volumetrically, in order to maintain the same level of power and performance in an engine [8]. It was also reported that the use of biodiesel in a conventional diesel engine results in substantial reduction in un-burnt hydrocarbon (UBHC), carbon monoxide (CO), particulate matter (PM) emission, and oxides of nitrogen (NO X ) [9].…”
Section: Introductionmentioning
confidence: 99%